Physiological, technical, and time-motion responses according to small-sided game formats and pitch size variations in adolescent male soccer players: effects of biological maturity status - Cherni, Bilel; Marzouki, Hamza; Selmi, Okba; Chen, Yung-Sheng; Bouassida, Anissa; Chamari, Karim (Biology of Sport, 2025)
We examined the impact of biological maturity status ((pre-, circa- and post-peak height velocity (PHV)) on time-motion, physiological and technical responses of under-15 soccer players during different small-sided game (SSG) formats performed on different pitch sizes. Thirty-six players (n = 12 per biological maturity group) performed 3- and 4-a-side SSGs on regular (36 × 27 m, 40 × 30 m, respectively) and large (40 × 29 m, 44 × 33 m, respectively) pitches. Total distance (TD), peak velocity, accelerations (Accl) > 2.5 m · s−2, decelerations (Dec) > 2.5 m · s−2, distances covered at different speeds (0 to < 7.0, 7.0 to < 14.0, 14.0 to < 18.0, and ≥ 18.0 km · h−1), peak heart rate (HRpeak), HRmean (expressed as percentage of HRmax), rating of perceived exertion (RPE), post-SSG blood lactate concentration (BLa), and technical actions were recorded. There was a biological maturity effect on RPE, HRmean (%HRmax), percentage of successful passes (%SP), and interceptions, with pre-PHV players showing higher RPE and interception scores in large SSG formats (p < 0.05), and post-PHV players demonstrating higher HRmean (%HRmax) and %SP on regular and large 3-a-side and 4-a-side pitches (p < 0.05). Across all biological maturity groups, 4-a-side resulted in higher TD, distances covered at different speeds and ball-loss scores, and lower Accl, Dec, BLa, %SP, and duel scores than 3-a-side SSGs (p < 0.05) for both pitch sizes. On large pitches, 3-a-side SSGs resulted in higher ball possession, interception, and RPE scores (p < 0.05), while regular pitch sizes favoured higher Accl and Dec in both 3- and 4-a-side SSGs (p < 0.05). Large SSG formats generally outperformed regular formats in time-motion metrics. Our findings underscore the importance of considering both biological maturity and game format when designing training sessions for youth soccer players.